An Overview of Sexual Desire Among People Living with HIV (PLHIV) at RSUD Toto Kabila - Rahim, Nirwanto K; Jumatrin, Nur Fitriah (Universitas Negeri Gorontalo, 2025)
Sexual desire is a fundamental component of quality of life, including for people living with HIV (PLHIV) who have experienced increased life expectancy through antiretroviral therapy (ART). However, the sexual dimension of PLHIV is often overlooked in healthcare services. This study aimed to describe the level of sexual desire among PLHIV at RSUD Toto Kabila. The research employed a quantitative descriptive approach using a cross-sectional survey design. The sample was obtained through total sampling, involving all 35 registered PLHIV at the hospital. The instrument used was the Sexual Desire and Erotic Fantasies Questionnaire (SDEF), which had been previously validated and officially translated. Univariate analysis was conducted and presented in frequency distributions. Results showed that the majority of respondents (57%) had a high level of sexual desire, while the remaining 43% had a low level. These findings indicate that sexual desire remains significant among PLHIV and may be influenced by clinical stability, psychosocial support, and self-acceptance. The discussion emphasizes the importance of holistic HIV services that are sensitive to patients' sexual health needs. This study concludes that fulfilling the sexual needs of PLHIV should be considered an essential aspect in efforts to improve their overall quality of life..